Lecturers’ Persepctives on Using Rubric Scoring in Preventing Internet Cheating at University Level - Zurniti, Vivi; Astuti, Indri; Burhan, Kistian (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Technological advances and developments in the era have created new challenges for lecturers in English language learning. As a result of the use of technological tools increasingly entering all aspects of life including learning, one of the things that have happened lately is cheating on computers or the internet. Computer and internet cheating are phenomenon of technological world involving human educational live. It cannot be avoided as the consequence of current development. However, one of the tools that can be used to address this issue is the assessment rubric. Assessment rubrics can help lecturers in assessing student assignments, making it easier for them to provide assessments. In relation to the use of computers or internet networks in creating writing assignments, scoring rubrics can help lecturers in assessing and identifying cheating activities from the internet or internet cheating. This study used descriptive analysis with a participant action research (PAR) approach. Data collection was carried out by interviewing three English lecturers who teach in non-English departments in general basic courses. The respondents were interviewed to obtain research results. The results were analyzed using the average formula. From the results of the study, it was found that the use of scoring rubrics can help lecturers in assessing and preventing plagiarism from the internet. or English assignments obtained from cheating from the internet.